An empirical assessment of the 2004 EU merger policy reform - Tomaso Duso; Klaus Gugler; Florian Szücs (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2012)
We propose a general framework to assess merger policy effectiveness based on standard oligopoly theory and stock market reactions. We focus on four different dimensions of effectiveness: 1) legal certainty, 2) decision errors, 3) reversion of anti-competitive rents, and 4) deterrence. We apply this framework to 368 merger cases scrutinized by the European Commission (EC) between 1990 and 2007. To evaluate the economic impact of the change in European merger legislation, we compare the results of the four tests before and after its introduction in 2004. Our results suggest that the 'more economic approach' resulted in improved ex-ante predictability of decisions and a reduction of the frequency of type I errors. Merger policy enforcement deters anti-competitive mergers without over-deterring pro-competitive transactions. Yet, the policy shift away from prohibitions, which are effective as a policy tool and as a deterrent mechanism, does not seem to be well-grounded.
Keywords: L4; K21; C13; D78; 330; merger control; regulatory reform; EU Commission; event-study; Fusionskontrolle; Reform; Wirkungsanalyse; Wettbewerb; Schätzung; EU-Staaten